First record of the genus Copturomorpha Champion from the United States and a new species from Texas (Coleoptera: Curculionidae: Conoderinae) - Hespenheide, Henry A. (Zootaxa, 2011)
I was recently sent for determination a series of a species of conoderine weevils collected in south Texas by Ed Riley of Texas A & M University, as part of a survey of the insect fauna of the region funded by the Texas Parks and Wildlife Department. To my surprise, these specimens represent an undescribed species and the first record of the primarily Neotropical genus Copturomorpha Champion in the United States.